2018
DOI: 10.1016/j.jmoldx.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Analytical Handling Conditions and Small RNA Recovery from Urine for miRNA Profiling

Abstract: There are currently no standardized protocols for pre-analytical handling of urine to best preserve small RNA for miRNA profiling studies. miRNA is an attractive candidate as a potential biomarker because of the high level of stability in body fluids and its ability to be quantified on multiple high-throughput platforms. We present a comparison of small RNA recovery and stability in urine under alternate pre-analytical handling conditions and extend recommendations on what conditions optimize yield of miRNA fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Importantly, this time interval seems to be heavily reliant on the storage temperature and type of analyte (e.g., nucleic acids, proteins, lipds, etc.) [ 154 ].…”
Section: Extracellular Vesicles From Liquid Biopsies As a Source Omentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this time interval seems to be heavily reliant on the storage temperature and type of analyte (e.g., nucleic acids, proteins, lipds, etc.) [ 154 ].…”
Section: Extracellular Vesicles From Liquid Biopsies As a Source Omentioning
confidence: 99%
“…Taken together, several studies show that several pre-separation methodological issues have a remarkable influence on the yield, purity, and cargo profile of EVs isolated from urine samples [ 148 , 154 , 155 ]. Importantly, this impact is transversal to all studies regardless of the selected EV separation method.…”
Section: Extracellular Vesicles From Liquid Biopsies As a Source Omentioning
confidence: 99%
“…Alternately, urine held at 2 °C to 4 °C and processed within 24 h, as well as one-time freeze-thaw samples, may be used for miRNA profiling, however, a 5 min 37 °C sample equilibration to solubilize any precipitation for increased miRNA recovery is recommended. On the other hand, it is important to note that urine samples held at 37 °C for as little as four hours are significantly compromised and are not suitable for miRNA profiling [ 152 ].…”
Section: Sample Collectionmentioning
confidence: 99%
“…On the other hand, there are studies that prefer a double centrifugation protocol, first at 200× g followed by 1800× g for 10 min [ 153 ], or first low-speed centrifugation at 1600× g for 10 min followed by second high-speed centrifugation at 16,000× g for 10 min at 4 °C [ 136 ]. Two-step centrifugation at 200× g for 10 min followed by a second centrifugation at 1000× g for 10 min was also reported to be used [ 152 ]. After removal of any residual contaminants, the cell-free supernatants are usually stored at −80 °C until further analysis [ 152 , 203 , 204 ].…”
Section: Processing and Storage Of Biological Materialsmentioning
confidence: 99%
“…EV assays will need to be robust enough to withstand such transport and logistical limitations. Several studies have suggested that miRNAs either free or within EVs are remarkably stable when isolated from both plasma and urine [50,51], suggesting that miRNAs may be a more robust and pragmatic biomarker of disease, than EVs themselves.…”
Section: Assay Performance Characteristicsmentioning
confidence: 99%